2022
DOI: 10.21203/rs.3.rs-1490073/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting neuronal lysosomal dysfunction caused by β-glucocerebrosidase deficiency with an enzyme-based Brain Shuttle construct

Abstract: Biallelic mutations in GBA1 that lead to reduced β-glucocerebrosidase (GCase) activity result in the monogenic lysosomal storage disease Gaucher disease (GD). Variants in one GBA1 allele are the most common genetic risk factor for multiple synucleinopathies including Parkinson’s disease (PD). Therapies to increase GCase activity in the brain hold great promise for the treatment of these diseases. To this end, we have developed blood-brain barrier penetrant therapeutic molecules by fusing antibody moieties that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Delivery of recombi-nant enzyme to GBA1 KO cells by addition to the media, led to a transient increase in lysosomal GCase activity (Figure 3D, E) at 24 h, which diminishes over time as the enzyme is secreted from the cells into the media as the enzyme is unstable in neutral media. [47] We next showed that pharmacological perturbations to trafficking of GCase from the ER to lysosomes, induced by the known small molecules brefeldin A and monensin, [48,49] lead to a decrease in lysosomal GCase activity as measured using LysoFix-GBA (Figure S3). Further, using the pharmacological agent bafilomycin A, which leads to deacidification of lysosomes, results in an expected decrease in lysosomal GCase activity (Figure S3).…”
Section: Methodsmentioning
confidence: 94%
“…Delivery of recombi-nant enzyme to GBA1 KO cells by addition to the media, led to a transient increase in lysosomal GCase activity (Figure 3D, E) at 24 h, which diminishes over time as the enzyme is secreted from the cells into the media as the enzyme is unstable in neutral media. [47] We next showed that pharmacological perturbations to trafficking of GCase from the ER to lysosomes, induced by the known small molecules brefeldin A and monensin, [48,49] lead to a decrease in lysosomal GCase activity as measured using LysoFix-GBA (Figure S3). Further, using the pharmacological agent bafilomycin A, which leads to deacidification of lysosomes, results in an expected decrease in lysosomal GCase activity (Figure S3).…”
Section: Methodsmentioning
confidence: 94%
“…The senescence inducer S100A9, which is upregulated with age (Swindell et al., 2013), also co‐localizes and co‐aggregates with α‐SYN in 20% of Lewy bodies and 77% of neuronal cells in the substantia nigra of PD patients (Horvath et al., 2018). Additionally, GBA‐KO cells that exhibit elevated GluCer levels demonstrate upregulation of S100A9 (Gehrlein et al., 2023). This is noteworthy since S100A9 is implicated in the induction of cellular senescence (Shi et al., 2019) and is significantly upregulated in multiple aging murine and human tissues, including those in the central nervous system (Swindell et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For initial analysis of glucosylsphingosine (GluSph) levels in frozen pellets of untreated H4 cells, cells were lysed by addition of distilled water followed by protein precipitation with methanol, as described [8,62]. The dry lipid samples were reconstituted in a mixture of acetonitrile/water 90/10 (v/v) containing 1% DMSO.…”
Section: Lipidomic Analysismentioning
confidence: 99%
“…Analysis was performed via positive ion electrospray LC-MS/MS in multiple reaction-monitoring (MRM) mode, using deuterated compounds as internal standards. A Waters Xevo-TQ-S mass spectrometer connected to a complete Waters Acquity Iclass UPLC system was used as previously described, with a mixture of acetonitrile/methanol/water 40/40/20 (v/v/v) as the wash solvent [8,62]. Samples were analyzed on a BEH glycan amide column (100 × 2.1 mm, 1.7 μm particle size; Waters Corporation, Switzerland) with a flow rate of 0.25 mL/min and an oven temperature of 30°C.…”
Section: Lipidomic Analysismentioning
confidence: 99%
See 1 more Smart Citation